2020
DOI: 10.1186/s12896-020-00613-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation effect of Medicago sativa colonized by Piriformospora indica in the phenanthrene and cadmium co-contaminated soil

Abstract: Background: The coexistence of polycyclic aromatic hydrocarbons (PAHs) and heavy metals has deleterious effects on environmental quality. Few reports have studied the mechanisms of plant inoculation with Piriformospora indica to remediate PAH-metal co-contaminated soil by analyzing the chemical speciation of the contaminants. This study investigated the influence of the inoculation of Medicago sativa with P. indica to remediate soil co-contaminated with phenanthrene (a kind of PAH) and cadmium (a heavy metal) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2121
2121

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…These results are in full agreement with previous research which showed that PHE and pyrene (PYR) induced negative effects on the phytoextraction of Cd from Cd-spiked soil by the hyperaccumulator Sedum alfredii (Wang et al, 2012). Similarly, it has been reported that Cd accumulation in stems of Medicago sativa was reduced after soil contamination with PHE, which was probably caused by the accumulation of organic pollutants in roots, which hindered Cd transport from roots to aboveground parts (Li et al 2020). Thus, metals uptake capacity may be reduced due to the increased in pH.…”
Section: Phe Reduces Phytoextraction E Ciencysupporting
confidence: 92%
“…These results are in full agreement with previous research which showed that PHE and pyrene (PYR) induced negative effects on the phytoextraction of Cd from Cd-spiked soil by the hyperaccumulator Sedum alfredii (Wang et al, 2012). Similarly, it has been reported that Cd accumulation in stems of Medicago sativa was reduced after soil contamination with PHE, which was probably caused by the accumulation of organic pollutants in roots, which hindered Cd transport from roots to aboveground parts (Li et al 2020). Thus, metals uptake capacity may be reduced due to the increased in pH.…”
Section: Phe Reduces Phytoextraction E Ciencysupporting
confidence: 92%
“…Regardless of plants growing in salinity or drought stress, our results have shown that the interaction effects of using MWCNs and inoculation of plants with P. indica on decreasing the plant Pb and Cd concentration were positive and enhanced the plant growth in heavy metals-polluted soils [43] and consequently can improve the biodegradation of petroleum hydrocarbon in the soil [44]. However, abiotic stress, such as salinity or drought stress, negatively affects plant growth and physiology.…”
Section: Resultsmentioning
confidence: 69%
“…Unfortunately, the agricultural soils underwent the rapid degradation and depletion of nitrogenous matter responsible for plant growth following excessive use by field crops. This threat was overcome by different techniques such as intercropping [ 10 ], the use of PGPB, and natural phytoremediation [ 92 ]. In fact, the result of total nitrogen content in non-bioprimed and bioprimed salt-treated plants and untreated plants clearly showed that the bacterial treatment before germination significantly improved the plant’s capacity to assimilate nitrogen from the soil under salt stress.…”
Section: Discussionmentioning
confidence: 99%